INVESTASI REKSA DANA DENGAN SISTEM MUDHARABAH OLEH PT.BANK SYARIAH MANDIRI PEKALONGAN - Agus Maulana Ramdhono, A. Tulus Sartono, Muhyidin (Diponegoro Law Journal, 2012)
Mutual Fund is an organization that works for the small investor to take part in the investment world. Mutual Funds Sharia comes to meet the needs of investors to income derived from the investment of funds could be accounted for religious. Implementation of Shariah Fund has similarities to conventional mutual fund. The basic thing that distinguishes them among other application-contract agreement (engagement) Islam in its operational mechanism. Arrangements regarding the application of the agreement set forth in Sharia Fund DSN-MUI Fatwa No.20/DSNMUI/IV/2001. Under the decree, agreement occurring in Mutual Funds Sharia al-wakalah (representative) and mudaraba (profit sharing). Based on the description, the authors are interested in conducting a study entitled "Mutual Fund Investing System With PT Bank Syariah Mandiri Mudaraba By Pekalongan branch". The formulation of the problem studied, namely: how the application of the Mutual Fund mudaraba PT. Bank Syariah Mandiri branch Pekalongan?, How ahambatan that arise in the application of the principle of mudaraba by PT Bank Syariah Mandiri branch Pekalonagan? This study uses empirical juridical approach is a method research approach to solve the problem denagan conduct research on primary data that exist in the field. On the implementation of Sharia Fund was still bias on a particular understanding of mudaraba system many people are still unfamiliar to the mutual fund products Syariah.hal This has become an important task for the PT. Bank Syariah Mandiri branch Pekalongan to promote products and Shariah Investment Fund meningkatkanya growth based Islamic investment in Indonesia, especially in Islamic Fund.